Beyond Engagement: Promoting non-monetary social relevance in contemporary academic departments - Mengie M Parker; Carrie Longley (Academic Chairpersons Conference Proceedings, 2017)
This presentation outlines methods of creating academic social relevance that are not based on simple monetary value thereby affording academic departments a measure of protection against undue resource attenuation. The presentation provides methods of promoting both internal and external social relevance as well as methods for measuring and reporting growth in departmental social relevance.
Keywords: Social Relevance; Stability; Resilience; Growth